Analysis of Relationship Between Cerebral Vascularization, Asymmetry and Paw Preference by Morphometric Techniques - Kutlu, Necip; Bayazıt, T. Onur; Giray, S. Gülşen (Fırat University, 2002)
Aim: Recent studies demonstrated that there is a correlation between cerebral asymmetry and paw preference. In addition, there is another hypothesis about relationship between vascularity of cerebral hemisphere, it is not investigated by morphometric studies. The aim of this study was to investigate the relation between cerebral asymmetry and paw preference by morphometric studies. Material and Methods: Paw preference was determined by the food reaching test in Wistar rats, which their wheight avarage was 200-350 g. The movement of right and left paw was determined every day for totally ten days. The data of the paw preference was analysed by the statistical test, so the paw preference of each animal was found. After assessment of paw preference, the rats sacrificed and the brains were removed by craniotomy without separation of each hemisphere, and the whole brain was fixed in 10% formalin. After the tissues were performed routine paraffin embedding, 5 micrometer sections from the blocks were stained with Hematoxylene-Eosin. The volumes and lengths of the capillary of the cortex and the medulla in both hemispheres were estimated by Cavalieri techniques dependent on "blind basis" theory. Results: There were a significant difference between two hemispheres with respect to capillary volume and lengths, while the volumes of the cortex and medulla was similar. Conclusion: It was concluded that cortex asymmetry capillary was positive correlated with paw preference.

Amaç: Son yıllarda yapılan çalışmalar serebral asimetri ile pençe tercihi arasında bir ilişki olduğunu göstermiştir. Bununla beraber asimetri ile beyin hemisferlerinin bölgesel olarak kanlanmasının da asimetrik olabileceği düşünülmüşse de, değerlendirilmesi sayısal olarak yapılmamıştır. Bu çalışmada, sıçanlarda serebral asimetri ile pençe tercihi arasındaki ilişkinin morfolojik olarak incelenmesi amaçlanmıştır. Gereç ve Yöntem: Ortalama ağırlıkları 200-350 gr olan Wistar cinsi sıçanların pençe tercihi besine uzanma testi ile belirlendi. Sağ ve sol pençe hareketleri her gün toplam elli kez olmak üzere 10 gün süreyle tekrarlanarak yapıldı. Veriler istatistiksel analize tabi tutularak hayvanların pençe tercihi saptandı ve sakrifiye edildikten sonra hayvanlardan kraniyotomi yöntemi ile her iki hemisfer ayrılmadan çıkarıldıktan sonra %10 `luk formalin ile tespit edildi. Rutin parafin takibinden sonra dokulardan alınan 5mikrometrelik seri kesitler Hematoksilen-Eosin ile boyandı. Her iki hemisferin kapiller volüm ve uzunlukları ile beyaz ve gri cevher alanları "Blind basis" teorisine dayalı olarak Cavalieri yöntemi ile incelendi. Bulgular: Sağ ve sol hemisfer kortekslerinin damarsal yapılar açısından karşılaştırılmasında damar hacim ve uzunluk farkları istatistiksel olarak anlamlı iken, medulla elde edilen aynı verilerde herhangi bir farklılık gözlenmedi. Sonuç: Kortikal asimetrik damarlanma ile pençe tercihi arasında pozitif bir korelasyon olabileceği düşünülmektedir.
Serebral Asimetri ile Pençe Tercihi Arasındaki İlişkinin Vaskülarizasyon Yönünden Morfometrik Yöntemlerle İncelenmesi